STRATEGI MARKETING POLITIK PASANGAN NINA AGUSTINA DAN LUCKY HAKIM PADA PILKADA KABUPATEN INDRAMAYU TAHUN 2020 - Rega Aji Sampurna, (2023)
This paper aims to understand the political marketing carried out by Nina and Lucky Hakim in the 2020 Indramayu District Election by using Niffeneger's political marketing theory and Adman Nursal's political marketing strategy. The research method used is a qualitative method with a descriptive qualitative approach. The descriptive qualitative approach aims to describe the political marketing and political marketing strategies carried out by the pair Nina and Lucky Hakim in the 2020 Indramayu District Election. The data sources used are primary data through interviews with the success team between H. Sirojudin, Nanang Qosim, and Kyai Sidiq and the Bawaslu, Pak Nurhadi. This research uses secondary data in the form of literature, documentation, or documentary archives.The final result of this study is that the political marketing strategy that is very dominant or used by Nina Agustina and Lucky Hakim is Push Marketing, in the form of blusukan or door to door both in traditional markets and in every village. Apart from that, Lucky's popularity has added to his own enthusiasm for Indramayu residents, especially mothers. This is seen as good news from the push marketing process to support the victory of the Nina and Lucky pair in the 2020 regional elections. However, on the other hand, there is a big role for the success team or the volunteer team for the Nina and Lucky pair, this big role has helped run the campaign until the end. Nina and Lucky won their victory in the 2020 Pilkada and the successful team took part in going down to the community with the branding of Nina and Lucky in the eyes of the public.